EFFECT OF STUDENT PERCEPTION OF ECONOMIC EFFECTIVENESS OF LEARNING OUTCOMES LEARNING LESSONS ECONOMY I SEMESTER IN CLASS XI SMA PGRI I PADANG - Leni, Leni; Ansofino, Ansofino; Jolianis, Jolianis (Pendidikan Ekonomi, 2013)
AbstractÂ The low student learning outcomes are caused by many factors, including the lack of good student perceptions and learning effectiveness to learning economics. One of the efforts made by the teacher to student learning outcomes is by telling the students that the lessons are not too difficult economy, so the perception of students and the effectiveness of learning in order to better student learning outcomes are also good / will increase.The purpose of this study was to determine the effect of students perceptions of the learning outcomes of students in high school economics PGRI I Padang, to determine the effect of the learning effectiveness of the learning outcomes of students in high school economics I PGRI Padang and to determine the effect of perception of students and the effectiveness of learning together terhadab learning outcomes of students in high school economics PGRI I Padang.Based on the data analysis conducted in the form of hypothesis testing, where the value obtained F_hitung = 83.831 and obtained values of 3.10 F_tabel, then F_hitung> F_tabel and significant value <the value of Î± (5%) ie 0.00 <0.05 means H_a hypothesis accepted. So the perception of students and the effectiveness of the learning economy posirif significant effect or influence on learning outcomes of students in high school economics PGRI I Padang.Â Keywords : Student Perceptions, Learning Effectiveness and Learning Outcomes